DOI: 10.22215/etd/2013-07313
|View full text |Cite
|
Sign up to set email alerts
|

Biologically informed disciplines : a comparative analysis of terminology within the fields of bionics, biomimetics, and biomimicry

Abstract: The author has granted a non exclusive license allowing Library and Archives Canada to reproduce, publish, archive, preserve, conserve, communicate to the public by telecommunication or on the Internet, loan, distrbute and sell theses worldwide, for commercial or non commercial purposes, in microform, paper, electronic and/or any other formats. AVIS: L'auteur a accorde une licence non exclusive permettant a la Bibliotheque et Archives Canada de reproduire, publier, archiver, sauvegarder, conserver, transmettre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 22 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…The lack of a single unifying theory and methodology in this space is often reported in the discourse (Bar-Cohen, 2011;Iouguina, Dawson, Hallgrimsson, & Smart, 2014;Mazzoleni, 2013;Myers, 2012). Iouguina (2013) observed that the overarching BID field has emerged from interdisciplinary practice-based research that is clumsily positioned among misinformed and ambiguous terminologies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The lack of a single unifying theory and methodology in this space is often reported in the discourse (Bar-Cohen, 2011;Iouguina, Dawson, Hallgrimsson, & Smart, 2014;Mazzoleni, 2013;Myers, 2012). Iouguina (2013) observed that the overarching BID field has emerged from interdisciplinary practice-based research that is clumsily positioned among misinformed and ambiguous terminologies.…”
Section: Discussionmentioning
confidence: 99%
“…The diverse range of meanings for a small number of terms (polysemy) is a significant factor that contributes to terminological disharmony; a systemic issue within scholastic BID discourse as reported by several scholars (Lepora, Verschure and Prescott, 2013;Vincent, 2014;Vincent, 1997;Vincent et al, 2006;Kapsali, 2016;Wahl, 2006;Iouguina, 2013). This phenomenon was studied by Iouguina, Dawson, Hallgrimsson and Smart (2014) using a combination of lexical semantic theory and ethnographic methods.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations